Studi Kasus di Indonesia: Kepatuhan Pengisian Clinical Pathway Stroke Iskemik dan STEMI di Beberapa Rumah Sakit Tahun 2019 - Telly Purnamasari Agus; Made Ayu Lely Suratri; Tetra Fajarwati (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2021)
A clinical pathway (CP) is a flow of clinical service provided to patients from entering to leaving the hospital. Clinical pathways are needed as an effort to improve the quality and control the cost of services in hospitals. Some hospitals that have developed CP have not fully implemented it to patients. On the other hand, hospitals that have implemented CP, still encounter general problems, such is low compliance with CP. The purpose of this study was to obtain an overview of compliance with filling out the clinical pathway (CP) form for ischemic stroke and ST-Elevation Myocardial Infarction (STEMI) cases in several hospitals in Indonesia. The research was conducted in public and private hospitals class A and B which have implemented CP for ischemic stroke and STEMI in 2019. Data collection was carried out in 20 hospitals spread across 11 provinces in 5 regions. The research is a case study using a mix method design. Quantitative data collection was carried out by observing/checking the CP form document for ischemic stroke and STEMI, to determine compliance in filling out of ischemic stroke and STEMI CP forms. Compliance is measured in five care services, namely medical care, nursing, support, pharmacy and nutrition. It is stated as compliant if the percentage of filling in the CP is ≥80%. The total number of 1094 CPs consisted of 681 ischemic ischemic stroke CPs and 413 STEMI CPs. The results showed that: 1). Compliance with implementing ischemic stroke CP is very low, only 32 out of 681 (5%) CP filled ≥80% in five care services, 2). Compliance with implementing STEMI CP is also very low, only 81 out of 413 (20%) CP filled ≥80% in five care services.The conclusion of the study showed that compliance with filling CP ischemic stroke and CP STEMI was very low, as measured by 5 types of care services (medical care, nursing care, supporting care, pharmaceutical care, and nutritional care). Abstrak Clinical pathway (CP) merupakan suatu alur pelayanan klinik yang diberikan pada pasien sejak masuk hingga keluar rumah sakit. Clinical pathway diperlukan dalam upaya meningkatkan mutu dan pengendalian biaya pelayanan di rumah sakit. Beberapa rumah sakit yang telah mengembangkan CP belum seluruhnya mengimplementasikan pada pasien. Di sisi lain rumah sakit yang telah mengimplementasikan CP, masih menemui kendala umum yaitu rendahnya kepatuhan terhadap CP. Tujuan penelitian untuk memperoleh gambaran kepatuhan pengisian formulir clinical pathway (CP) kasus stroke iskemik dan ST-Elevation Myocardial Infarction (STEMI) di beberapa rumah sakit di Indonesia. Penelitian dilakukan di rumah sakit pemerintah dan swasta kelas A dan B yang telah mengimplementasikan CP kasus stroke iskemik dan STEMI pada tahun 2019. Pengumpulan data dilakukan di 20 rumah sakit yang tersebar di 11 provinsi dalam 5 regional. Penelitian berupa studi kasus menggunakan desain mix method. Pengumpulan data kuantitatif dengan cara melakukan observasi/ cek dokumen formulir CP stroke iskemik dan STEMI, untuk mengetahui kepatuhan dalam mengisi formulir CP stroke iskemik dan STEMI. Kepatuhan diukur pada lima asuhan pelayanan yaitu asuhan medis, keperawatan, penunjang, farmasi dan nutrisi.. Dikatakan patuh jika persentase pengisian CPterisi ≥80%. Jumlah total 1094 CP terdiri dari 681 CP stroke iskemik dan 413 CP STEMI. Diketahui dari hasil penelitian bahwa: 1). Kepatuhan melaksanakan CP stroke iskemik sangat rendah, hanya 32 dari 681 (5%) CP terisi≥80% pada lima asuhan pelayanan 2). Kepatuhan melaksanakan CP STEMI juga sangat rendah, yaitu 81 dari 413 (20%) CP terisi ≥80% pada lima asuhan pelayanan. Kesimpulan penelitian menunjukkan bahwa kepatuhan pengisian CP stroke iskemik dan CP STEMI sangat rendah, yang diukur dari 5 jenis asuhan pelayanan (asuhan medis, asuhan keperawatan, asuhan penunjang, asuhan farmasi, dan asuhan nutrisi).